LARP-1 promotes oogenesis by repressing fem-3 in the C. elegans germline - Zanin, Esther; Pacquelet, Anne; Scheckel, Claudia; Ciosk, Rafal; Gotta, Monica (Journal of Cell Science, 2010)
LA-related protein 1 (LARP-1) belongs to an RNA-binding protein family containing a LA motif. Here, we identify LARP-1 as a regulator of sex determination. In C. elegans hermaphrodites, a complex regulatory network regulates the switch from sperm to oocyte production. We find that simultaneous depletion of larp-1 and the Nanos homologue nos-3 results in germline masculinization. This phenotype is accompanied by a strong reduction of the levels of TRA-1, a GLI-family transcription factor that promotes oogenesis. TRA-1 levels are regulated by CBCFEM-1, a ubiquitin ligase consisting of the FEM proteins, FEM-1, FEM-2 and FEM-3 and the cullin CUL-2. We show that both the masculinization phenotype and the reduction of TRA-1 levels observed in nos-3;larp-1 mutants require fem-3 activity, suggesting that nos-3 and larp-1 regulate the sperm-oocyte switch by inhibiting the fem genes. Consistently, fem-3 mRNA levels are increased in larp-1 mutants. By contrast, levels of fem-3 mRNA are not affected in nos-3 mutants. Therefore, our data indicate that LARP-1 and NOS-3 promote oogenesis by regulating fem-3 expression through distinct mechanisms.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Caenorhabditis elegans; FEM proteins; La-motif; LARP-1; Nanos; NOS-3; Sex determination; TRA-1